Development Of A Mobile-Based Digital Attendance System For Employees Of The Public Works Department Of Bengkulu City - Yanto, Febi Febri; Rifqo, Muhammad Husni; Muntahanah, Muntahanah; Imanullah, Muhammad (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Attendance is one of the important performance assessments. Absenteeism carried out by each employee can affect every employee throughout the agency. The Bengkulu City Public Works Department wants to carry out reforms. The attendance system for each employee uses digital-based attendance. The attendance system developed in this research is based on mobile technology. The aim of this research is to enable employees to take attendance via their mobile devices with mobile features to ensure attendance is taken at the right location. Test results show that this system has succeeded in increasing the efficiency of the attendance process, reducing recording errors, and enabling real-time monitoring of attendance by the office admin. Thus, it is hoped that the development of a mobile-based digital attendance system can be an effective solution in managing employee attendance more efficiently and accurately.